2022
DOI: 10.21203/rs.3.rs-1551751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial studies of the response of rubber tree seedlings treated with saprobic fungi from the semiarid region of Northeast Brazil to anthracnose

Abstract: Anthracnose, caused by fungi of the genus Colletotrichum, is present in the main areas where rubber trees (Hevea brasiliensis) are planted. Thus, considering that biological agents can be an alternative for disease control, the present study aimed to carry out initial studies to investigate the response of rubber tree seedlings inoculated with Colletotrichum and treated with saprobes fungi from the semiarid region of Northeast Brazil (Curvularia eragrostidis, Memnoniella levispora, Myrothecium roridum and Phia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Differently from their response to powdery mildew, except for HbPAL3 and HbPAL6 with no change in expression, all other HbPALs were down-regulated in anthracnose-infected leaves. Bergamini Lopes et al [40] showed that the activity of PAL was enhanced after treatments that strengthened anthracnose resistance in rubber trees. Therefore, we speculate that the susceptibility to anthracnose may be related to the decrease in HbPAL expression in the rubber tree.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from their response to powdery mildew, except for HbPAL3 and HbPAL6 with no change in expression, all other HbPALs were down-regulated in anthracnose-infected leaves. Bergamini Lopes et al [40] showed that the activity of PAL was enhanced after treatments that strengthened anthracnose resistance in rubber trees. Therefore, we speculate that the susceptibility to anthracnose may be related to the decrease in HbPAL expression in the rubber tree.…”
Section: Discussionmentioning
confidence: 99%
“…velezensis secreted HN-2 elicitors into rubber leaves; these elicitors enhance plant immunity by suppressing HbLFG1 and elevating the activity of antioxidant enzymes such as ascorbate peroxidase, peroxidase, catalase, and superoxide dismutase [52]. When treated with the saprobic fungal antagonists Curvularia eragrostidis and Phialomyces macrosporus, phenylalanine ammonia lyase activity was higher in rubber tree, which enhanced plant resistance against the anthracnose pathogen C. tamarilloi [39]. Class III peroxidases are associated with defense responses to P. meadii; their activity in rubber leaves can be induced by Alcaligenes sp.…”
Section: Induced Plant Resistancementioning
confidence: 99%